Clinical characteristics of preterm and term infants with Ureaplasma in gastric fluid - Yoshiichi Abe; Masanori Inoue; Kazuhito Sekiguchi; Satoko Nakano; Yasuhiro Tomaru; Tomoki Maeda; Norio Shimizu; Kenji Ihara (Pediatrics and Neonatology)
Background: Ureaplasma spp. is an endemic microorganism that causes placental chorioamnionitis or preterm delivery in pregnant women, and the occurrence of bronchopulmonary dysplasia or intraventricular hemorrhaging in preterm infants after birth, although the pathogenicity of Ureaplasma remains controversial. The association between Ureaplasma exposure and the symptoms or outcomes of infected mothers or their infants born at term remains poorly understood. We investigated the clinical characteristics of preterm and term infants with or without Ureaplasma in their gastric fluid. Methods: Gastric fluid samples were collected from 47 newborns in the neonatal intensive-care unit immediately after birth and tested using multiplex polymerase chain reaction (PCR) assays targeting Ureaplasma spp., Ureaplasma parvum, and Ureaplasma urealyticum. The clinical findings and outcomes of the neonates and their mothers were retrospectively evaluated. Results: Ureaplasma spp. were detected in 9/47 samples (19%) by multiplex PCR assays. In all cases, the subspecies was U. parvum. The Ureaplasma-positive group had a significantly higher incidence of chorioamnionitis in utero than the Ureaplasma-negative group. Regarding preterm infants, the IgM levels in the Ureaplasma-positive group were significantly higher than in the Ureaplasma-negative group. In contrast, in term infants, the rates of a non-reassuring fetal status, a maternal fever, and maternal leukocyte counts and maternal C-reactive protein levels within five days before delivery in the Ureaplasma-positive group were significantly higher than those in the Ureaplasma-negative group. All three extremely-low-birth-weight infants with Ureaplasma developed bronchopulmonary dysplasia. The length of hospitalization in the Ureaplasma-positive group was almost same as that in the Ureaplasma-negative group for term infants. Conclusion: Mothers or their fetuses with exposure to Ureaplasma expressed characteristic clinical features during pregnancy and after birth.